Endogenous retroviruses lead to the expression of a histocompatibility antigen detectable by skin graft rejection. - Colombo, M P (1987)
Mov mouse strains differ from their respective, coisogenic partner strains by the embryonic, germ-line introduction of Moloney murine leukemia virus genomes. The possibility that retroviral insertions into the mouse genome resulted in gain or loss mutations at non-H-2 histocompatibility loci was investigated by reciprocal skin grafting between Mov mice and mice from coisogenic, background strains. Two B6-derived and eight 129-derived Mov strains were analyzed. B6 mice rejected skin from the viremic Mov-3 and Mov-14 strains, indicating that these mice had new histocompatibility antigens. No rejections were observed with reciprocal skin grafts exchanged between mice of the 129 background strain and 129-derived Mov strains, one of which (Mov-9) is viremic. To investigate the potential viral origin of the new histocompatibility antigen in Mov-14, lymphocytes from B6 mice primed in vivo with Mov-14 cells or skin were restimulated in vitro with Mov-14 spleen cells and with two retroviral-induced B6 lymphomas, MBL-2 and RBL-5. All three cell types stimulated cytotoxic lymphocytes that lysed Mov-14 Con A lymphoblasts, MBL-2 and RBL-5. The same cytotoxic lymphocytes lysed only lymphoblasts from the viremic Mov-9 strain when tested on cells from 129 and 129 Mov mice. Thus the insertion and expression of exogenous Moloney murine leukemia virus results in the appearance of a new histocompatibility antigen as defined by its stimulation of skin-graft rejection and cytotoxic effector T-cell generation. The non-H-2 histocompatibility antigen identified in this study has been designated H-43 and is encoded by genes mapping to different loci in different Mov strains. These observations suggest that at least a subgroup of non-H-2 histocompatibility antigens is encoded by endogenous retroviruses; the implications of these results for understanding the origin and the identity of non-H-2 histocompatibility antigens are discussed.